IL-33/IL-33R in various types of carotid artery atherosclerotic lesions. (August 2019) - Stankovic, Milos; Ljujic, Biljana; Babic, Srdjan; Maravic-Stojkovic, Vera; Mitrovic, Slobodanka; Arsenijevic, Nebojsa; Radak, Djordje; Pejnovic, Nada; Lukic, Miodrag L.
Highlights: IL-33/ST2 pathway favourite formatting of carotid atherosclerotic plaque. Vulnerable/high-risk carotid plaques have increased expression of IL-33 and ST2. Levels of circulating IL-33 are increased in patients with carotid atherosclerosis. Abstract: Objective: Inflammation plays a crucial role in the progression of atherosclerotic plaques. The aim of the study was to investigate serum levels and expression of Interleukin-33 (IL-33) and ST2 receptor in atherosclerotic plaques and to analyze correlation with the type of the carotid plaques in patients with carotid disease. Methods: This study included 191 consecutive patients submitted for carotid endarterectomy (CEA). Preoperative serum levels of IL-33 and soluble ST2 (sST2) were measured. Atherosclerotic plaques obtained during surgery were initially histologically classified and immunohistochemical analyzes of IL-33, IL-33R, CD68 and alpha-SMA expression was performed. Ultrasound assessment of the level of carotid stenosis in each patient was performed prior to carotid surgery. Demographic and clinical data such as gender, age, smoking status, blood pressure, glycaemia, hemoglobin and creatinine levels, and comorbidities were collected and the comparisons between variables were statistically evaluated. Results: Serum levels of IL-33 (35.86 ± 7.93 pg/ml vs.12.29 ± 1.8 pg/ml, p < 0.05) and sST2 (183 ± 8.03 pg/ml vs. 122.31 ± 15.89 pg/ml, p < 0.05) were significantly higher in the group of CEA patients vs. healthy subjects. We demonstrated abundant tissue expression of IL-33 and ST2 in atherosclerotic carotid artery lesions. The levels of IL-33 and IL-33R expression were significantly higher in vulnerable plaques and significantly correlated with the degree of inflammatory cells infiltration in these plaques (R = 0.579, p = 0.049). Immunohistochemical analysis also revealed that cells responsible for IL-33 expression are not only mononuclear cells confined to inflammatory atherosclerotic lesions, but also smooth muscle cells which gained phenotypic characteristics of foam cells and were loaded with lipid droplets. Conclusion: The obtained results confirm the importance of IL-33/ST2 axis in the process of atherosclerosis, and indicate its ambiguous function in immune response, whether as proinflammatory cytokine in advanced atherosclerotic lesions, or as profibrotic, in early lesions.